Actuality and countermeasure of the advertisement market by sport stars - Li, B. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: The purpose of this study is to determine how the advertisement market made by sport stars enables development to occur reasonably, smoothly, orderly and steadily. Sport stars, being lively, healthy, active and enterprising, and their commercial values can not escape the appetites of any enterprise or company. The cooperation mechanism between sport stars and enterprise has a long way to go to achieve excellence and demonstrates lack of construction and feasibility. This approach prevents facing the market with the best model of cooperation. Methods Study data was based on a literature review and expert interviews. Results This study outlines the actuality and countermeasures used in the advertisement market by analyzing its beginning, actuality and characteristics. The analysis included star effect, commercial value, the star's gains in income and reputation, relative sport or brand type, management, issues and cooperation mechanism. The sport stars advertisement market in China sprang up later than in other countries. The earlier advertisement focused on sport competitions and performance in the form of print, crown and product, which has little relationship with athletes. Improvement in competitive sport and good results in the Olympic and World competitions have advanced the advertising market involving sport stars. More than 50 sport stars in more than 10 sports have advertised for the market. Advertising has changed its format from material to person and from single sports to multi-sports. By advertising, sport stars can not only bring economic benefits to the companies but also to themselves. The development of market advertising enhances the development of the sports industry. The market is developing quickly, although there are still some blind spots and shortcomings in the system, such as system income distribution and rights of participants. Conclusions Coupling the deepening reform and more open policy with the booming market economy provides an expansive space for the advertisement market by sport stars. This approach requires more for the stars' overall development, in areas such as public influence, personality and charm, physique, temperament, moral character and performance skills.. Sport stars can not only develop their material assets but also obtain social and economic values through involvement in advertisements. The interference of the sports agency is the inevitable result of the sports market, which makes the market develop more smoothly and orderly. However, the market needs progressive improvement and regulation, especially in systems and management processes.